The nursery-web spider Hygropoda tanganus (Roewer, 1955) comb. nov. (Araneae: Lycosoidea: Pisauridae); generic transfer, first description of the female and redescription of the male - Da Silva, Estevam L. Cruz (Zootaxa, 2013)
The genus Hygropoda Thorell, 1894 comprises 27 known species, which are distributed in the Australasian, Afrotropical and Oriental zoogeographical regions (Platnick 2013), with the majority of species described from the latter region. Currently, no modern monographic revision reviewing all species assigned to the genus exists and putative apomorphies of the genus, except for the flexible tarsi, have not been assessed.